2004
DOI: 10.1002/bies.20143
|View full text |Cite
|
Sign up to set email alerts
|

The source(s) for new pancreatic beta cells in adult life

Abstract: The natural source for new pancreatic beta cells is an important issue both for understanding the pathogenesis of diabetes, and for possibly curing diabetes by increasing the number of beta cells. Dor et al. investigated beta-cell renewal and regeneration by genetic lineage analysis in mice during physiological growth and after partial pancreatectomy. The data conclusively showed that beta-cell replication was the only source for new beta cells without contributions from stem cells or other non-beta cells. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…This is suggestive of an inferior regenerative capacity, as previously indicated by some authors (Bouwens, 1998). In fact, some researchers have hypothesized that the β-cells in the islets originate from migrating acinar cells, and that there are no regenerative stem cells in the islets (Bouwens, 1998;Bock, 2004). In contrast, other authors have reported the existence of replication within the islets (Magami et al, 2002).…”
Section: Discussioncontrasting
confidence: 41%
“…This is suggestive of an inferior regenerative capacity, as previously indicated by some authors (Bouwens, 1998). In fact, some researchers have hypothesized that the β-cells in the islets originate from migrating acinar cells, and that there are no regenerative stem cells in the islets (Bouwens, 1998;Bock, 2004). In contrast, other authors have reported the existence of replication within the islets (Magami et al, 2002).…”
Section: Discussioncontrasting
confidence: 41%
“…There are multiple mechanisms involved in beta cell renewal [5][8], [31] and much effort has been devoted to identifying those growths factors that can potentially promote and support beta cell regeneration. However, the key signals triggering beta cell replication and regeneration still remain to be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Beta cell renewal may take place by differentiation of stem cells [5], [6] or by replication of existing differentiated cells, of the same [7] or of a different lineage [8]. The favored mechanism/s may be determined by the nature of the demand or initial injury [9].…”
Section: Introductionmentioning
confidence: 99%
“…This region shares 88% similarity with the human sequence (Brink et al 2001, Brink & Gruss 2003. Pax4 expression was shown to be dependent on the concerted action of the key pancreatic transcription factors Pan1, Beta2/ NeuroD, hepatic nuclear factor (HNF)-1a, HNF-4a, pancreatic duodenal homeobox (Pdx)1 and E47/E12 interacting with the proximal promoter (Smith et al 2000, 2004, Kanno et al 2006. A further increase in transcription was observed when Beta2/NeuroD was substituted by the early pancreatic committing transcription factor Ngn3 (Smith et al 2000(Smith et al , 2004.…”
Section: Pax4 As a Master Regulator Of Islet Developmentmentioning
confidence: 99%
“…The search for the regenerative b-cell or precursor pool that responds to metabolic demands has proved more challenging and controversial than anticipated (Bock 2004, Bonner-Weir et al 2004, Bonner-Weir & Sharma 2006. Indeed, depending on the experimental model and degree of injury inflicted to the pancreas, new b-cells were shown to be generated by neogenesis of ductal epithelium cells (Peshavaria et al 2006), by transdifferentiation of acinar cells (Lipsett & Finegood 2002, Minami et al 2005 and from intra-islet nestinpositive precursor cells (Zulewski et al 2001).…”
mentioning
confidence: 99%